Serum Endothelin-1 and Transforming Growth Factor-β Levels in the Newborns With Respiratory Distress - Derya Benzer; A. Denizmen Aygun; Ahmet Godekmerdan; A. Nese (Citak) Kurt; Saadet Akarsu; Erdal Yilmaz (Mediators of Inflammation)
The purpose of this present study was to evaluate the serum levels of ET-1 and TGF-β in the newborns with respiratory distress. In this study, newborns with respiratory distress hospitalized into the Newborn Intensive Care Unit were included. The highest values of ET-1 and TGF-β were obtained from newborns with diagnosis as meconium aspiration syndrome (5.70±5.87 pg/mL and 3.75±1.94 pg/mL, resp) in the sample obtained in the first six hours after birth, and these are statistically different from control group (P<.05). Also, same results were obtained for newborns with respiratory distress syndrome (3.37±1.59 pg/mL and 2.05±0.98 pg/mL, resp). After oxygen treatment, ET-1 values obtained in the first six hours of life were decreased regularly in the following days (P<.05). In the differentiating diagnosis of the respiratory distress of newborns, the investigation of ET-1 and TGF-β levels is meaningful. The ET-1 levels investigated in the first six hours is more useful in determining the prognosis, and repeating ET-1 levels in the following days is more meaningful to determine clinical response.